Faktor-faktor yang berkorelasi dengan stres kerja perawat di ruang rawat inap - Cahyaningrum, Ika; Sutriningsih, Ani; Uni, Ostaleni (Holistik Jurnal Kesehatan, 2025)
Background: Occupational stress is a common problem faced by nurses and can affect the quality of care, mental health, and work productivity. Purpose: To analyze factors correlated with occupational stress in nurses in the inpatient ward. Method: This study used a cross-sectional design and involved 84 nurses randomly selected from a total population of 118 nurses in the Inpatient Unit of Panti Waluyo Sawahan Regional Hospital. The instruments used were a questionnaire measuring respondent characteristics, the ISEL-12 social support questionnaire, and the Perceived Stress Scale (PSS) questionnaire measuring occupational stress. Results: Correlation tests showed no correlation between age (p=0.626), education level (p=0.244), and length of service (p=0.229) and nurses' occupational stress. However, there was a significant correlation between social support and nurses' stress (p<0.001; r=–0.449). The better the social support, the lower the level of occupational stress. Conclusion: There was no correlation between age, education level, and length of service with stress experienced by nurses in inpatient wards. However, there was a significant correlation between social support and the level of work stress experienced by nurses in inpatient wards. The better the social support provided, the lower the level of work stress experienced. Suggestion: Future research can examine other factors that may be associated with nurses' work stress, such as nurse workload, type of service, and workplace. Furthermore, hospital management is expected to implement interventions focused on improving nurses' well-being through emotional support, such as providing counseling services, sharing forums, and maintaining workload balance to address nurses' work stress.   Keywords: Inpatient Wards; Nurses; Work Stress.   Pendahuluan: Stres akibat pekerjaan adalah masalah yang sering dihadapi oleh perawat dan dapat memengaruhi mutu pelayanan, kesehatan mental, serta produktivitas kerja. Tujuan: Untuk menganalisis faktor-faktor yang berkorelasi dengan stres kerja perawat di ruang rawat inap. Metode: Studi ini menggunakan desain cross-sectional dan melibatkan 84 perawat yang dipilih secara acak dari total populasi sebanyak 118 perawat di unit Rawat Inap Rumah Sakit Panti Waluyo Sawahan. Instrumen yang digunakan adalah kuesioner yang mengukur karakteristik responden, kuesioner dukungan sosial ISEL-12, dan kuesioner yang mengukur stres kerja yaitu Perceived Stress Scale (PSS). Hasil: Uji korelasi menunjukkan bahwa tidak ada korelasi antara usia (p=0.626), tingkat pendidikan  (p=0.244), dan masa kerja (p=0.229) dengan stres kerja perawat. Namun, terdapat korelasi yang signifikan antara dukungan sosial dan stres yang dialami oleh perawat (p<0.001; r=–0.449), semakin baik dukungan sosial, maka semakin rendah tingkat stres kerja. Simpulan:  Tidak ada korelasi antara usia, tingkat pendidikan, dan masa kerja dengan stres yang dialami oleh perawat di ruang rawat inap. Namun, terdapat korelasi yang signifikan antara dukungan sosial dan tingkat stres kerja perawat di ruang rawat inap. Semakin baik dukungan sosial yang diberikan, maka semakin rendah pula tingkat stres kerja yang dialami. Saran:  Penelitian selanjutnya dapat meneliti faktor lain yang mungkin berhubungan dengan stres kerja perawat, seperti beban kerja perawat, jenis pelayanan, dan tempat bekerja. Selain itu, diharapkan pihak menejemen rumah sakit dapat melakukan intervensi yang berfokus pada peningkatan kesejahteraan perawat melalui dukungan emosional, misalnya menyediakan layanan konseling, forum sharing, dan untuk menjaga keseimbangan beban kerja untuk mengatasi stres kerja perawat.   Kata Kunci: Perawat; Ruang Rawat Inap; Stres Kerja.